Evaluating Access to Information, access to finances, firm competition and Small Medium Enterprise performance in South Africa: Array - MSOMI, Thabiso Sthembiso; Yearwood, Verna Melicent; Msomi, Mbali Portia (The Journal of Accounting and Management, 2022)
At the center of the poor performance of SMEs are the lack of access to information, inaccessibility of finances, and lack of firm competitiveness. Hence this study evaluates the access to Information, access to finances, firm competition, and Small Medium Enterprise performance in South Africa. This employed a quantitative approach which was supported by the positivist paradigm. The study used a sample size of 140 SMEs. SME owners or suitable representatives were selected using the purposive sample technique. The results of the study revealed a positive correlation between access to information, access to finances, and SME performance. On the other hand, a negative correlation between firm competition and SME performance was observed. The study recommended that financial institutions should remove the limit on the amount of money the SME may borrow if they have appropriate collateral. Also, financial institutions should employ realistic loan repayment procedures in order to attract more clients and so enhance credit access. Finally, the research and the study urge that the government considers providing incentives for SMEs by holding workshops, seminars, and conferences to strengthen SMEs ’ management abilities and keep them up to speed on continuous learning available in the market that would boost performance.